Female university students’ attitude toward fertility and childbearing in Vietnam - Thi Thu Ha Nguyen; Hoang Thanh Luong; Thi Thu Phuong Pham (Universa Medicina, 2026)
BackgroundPopulation aging and declining fertility rates are emerging concerns worldwide. In Vietnam, fertility rates have decreased rapidly in recent years. Understanding young women’s attitudes toward fertility and childbearing is important for developing appropriate reproductive and population policies. This study aimed to assess attitudes toward fertility and future childbearing among female students at the University of Medicine and Pharmacy, Vietnam National University, Hanoi. MethodsA cross-sectional online survey was conducted among 187 nulliparous female students from September 2024 to March 2025. Data were collected using the Attitudes Toward Fertility and Childbearing Scale (AFCS). Descriptive statistics, chi-square tests, independent t-tests, and one-way analysis of variance were used to analyze the data. ResultsOverall, 66.3% of participants expressed a desire for future childbearing, 23.0% were uncertain, and 10.7% did not desire children. The desire for future childbearing was significantly higher among students aged >22 years compared with those aged ≤22 years (85.1% vs. 60.0%) and among participants in a relationship compared with single students (79.5% vs. 62.2%). The mean scores for the AFCS domains “Importance of fertility for the future,” “Childbearing as a hindrance at present,” and “Female identity” were 3.41 ± 0.97, 3.90 ± 0.74, and 2.96 ± 0.93, respectively. Greater importance placed on future fertility was associated with older age, rural residence, cohabiting parents, and desire for children (p<0.05). ConclusionFuture childbearing intention among female students was relatively low and influenced by age and relationship status. Although fertility was considered important, childbearing was widely perceived as a present burden.